Optimal. Leaf size=28 \[ (2+e) \left (e^x-x+(-2+x) x^2\right )-\frac {e^2}{\log (x)} \]
________________________________________________________________________________________
Rubi [A] time = 0.32, antiderivative size = 38, normalized size of antiderivative = 1.36, number of steps used = 6, number of rules used = 4, integrand size = 58, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.069, Rules used = {6688, 2194, 2302, 30} \begin {gather*} (2+e) x^3-2 (2+e) x^2-(2+e) x+(2+e) e^x-\frac {e^2}{\log (x)} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
Rule 30
Rule 2194
Rule 2302
Rule 6688
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \left ((2+e) \left (-1+e^x-4 x+3 x^2\right )+\frac {e^2}{x \log ^2(x)}\right ) \, dx\\ &=e^2 \int \frac {1}{x \log ^2(x)} \, dx+(2+e) \int \left (-1+e^x-4 x+3 x^2\right ) \, dx\\ &=-((2+e) x)-2 (2+e) x^2+(2+e) x^3+e^2 \operatorname {Subst}\left (\int \frac {1}{x^2} \, dx,x,\log (x)\right )+(2+e) \int e^x \, dx\\ &=e^x (2+e)-(2+e) x-2 (2+e) x^2+(2+e) x^3-\frac {e^2}{\log (x)}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.03, size = 28, normalized size = 1.00 \begin {gather*} (2+e) \left (e^x+x \left (-1-2 x+x^2\right )\right )-\frac {e^2}{\log (x)} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.67, size = 49, normalized size = 1.75 \begin {gather*} \frac {{\left (2 \, x^{3} - 4 \, x^{2} + {\left (x^{3} - 2 \, x^{2} - x\right )} e + {\left (e + 2\right )} e^{x} - 2 \, x\right )} \log \relax (x) - e^{2}}{\log \relax (x)} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.17, size = 66, normalized size = 2.36 \begin {gather*} \frac {x^{3} e \log \relax (x) + 2 \, x^{3} \log \relax (x) - 2 \, x^{2} e \log \relax (x) - 4 \, x^{2} \log \relax (x) - x e \log \relax (x) - 2 \, x \log \relax (x) + e^{\left (x + 1\right )} \log \relax (x) + 2 \, e^{x} \log \relax (x) - e^{2}}{\log \relax (x)} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.04, size = 48, normalized size = 1.71
method | result | size |
default | \(-2 x +\left ({\mathrm e}+2\right ) {\mathrm e}^{x}-\frac {{\mathrm e}^{2}}{\ln \relax (x )}-4 x^{2}+2 x^{3}-2 x^{2} {\mathrm e}+x^{3} {\mathrm e}-x \,{\mathrm e}\) | \(48\) |
risch | \(x^{3} {\mathrm e}-2 x^{2} {\mathrm e}+2 x^{3}-x \,{\mathrm e}+{\mathrm e}^{x +1}-4 x^{2}-2 x +2 \,{\mathrm e}^{x}-\frac {{\mathrm e}^{2}}{\ln \relax (x )}\) | \(49\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.36, size = 48, normalized size = 1.71 \begin {gather*} x^{3} e + 2 \, x^{3} - 2 \, x^{2} e - 4 \, x^{2} - x e - 2 \, x - \frac {e^{2}}{\log \relax (x)} + e^{\left (x + 1\right )} + 2 \, e^{x} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 6.34, size = 42, normalized size = 1.50 \begin {gather*} {\mathrm {e}}^x\,\left (\mathrm {e}+2\right )-\frac {{\mathrm {e}}^2}{\ln \relax (x)}-x^2\,\left (2\,\mathrm {e}+4\right )-x\,\left (\mathrm {e}+2\right )+x^3\,\left (\mathrm {e}+2\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.31, size = 42, normalized size = 1.50 \begin {gather*} x^{3} \left (2 + e\right ) + x^{2} \left (- 2 e - 4\right ) + x \left (- e - 2\right ) + \left (2 + e\right ) e^{x} - \frac {e^{2}}{\log {\relax (x )}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________